Pengaruh Struktur Modal, Keputusan Investasi, dan Struktur Kepemilikan Terhadap Nilai Perusahaan - Chatrine Maria Isabrine; Sofie (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of capital structure, investment decisions, managerial ownership, and corporate ownership on firm value in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange for the period 2020–2023. The research employs a quantitative method using secondary data and a purposive sampling technique involving 32 companies, resulting in 102 observations. The analysis was conducted using multiple linear regression with the assistance of SPSS 25. The results show that capital structure and investment decisions do not have a significant effect on firm value. On the other hand, managerial ownership and corporate ownership have a positive and significant effect. These findings highlight the importance of ownership structure in enhancing firm value, particularly in sectors that are fundamentally stable.